Estimulação precoce domiciliar: um programa de intervenção e sua análise em bebês de risco de O a 6 meses - Braz, Patrícia Ferraz (Universidade Federal de São Carlos, 1999)
One of the highest risks to the newborn, according to several authors is Asphyxia, a progressive process potentially reversible in the initial stages, in a spontaneous way, if the cause is removed. However, once in progress, this spontaneous reverse process becomes difficult, for the most part, due to circulatory, metabolic and neurologic alterations that goes with it can lead to severa[ leveis of compromising in its development. There are matemity hospital conducts in the neonatal period that may detect any risk of alteration in its development. Under the risk of disabilities, it is necessary to refer the newbom to initiate an intervention as soon as possible, avoiding future disabilities and recuperation of those already installed. Based on its presumed above, it led the objectives of this research that intended to analyze the neuropsychomotor development of infants that participated in an early home intervention, relating with features of perinatal asphyxia detected in matemity hospital and, comparing with the literature data. The study had as participating, an experimental group (GE), and a control group (GC), composed on risky babies, with features of perinatal asphyxia, detected in the maternity hospital. The infants in the GE participated intervention program from 3'd week until 3'd month of life. The GE mothers, was also participants, since they were present in the stimulation process. All the infants (the GE and the GC) were submitted to assessments in neuropsychomotor development until the 24th week. The chosen place to the intervention was the own infant's home. The procedure consisted of 3 (three) stages: 1) an interoiew with the mothers of GE, with the objective to know the newbom routine; 2) an assessment of its neuropsychomotor development, realized in 2"-d, 3rd, 8th and 12th week, 1 (5th, 2()lh and 24th week of infants life and, 3) the GE global stimulation twice a weekfrom 3'd week until the 12th week. The results were achieved through analysis interventions before the aspects: (a) the researcher conducts, the infant's responses and the guidance supplied to the mother; (b) from development comparison of the infants in the GE along with its development; (e) from development comparison of the infants in the GE and the GC with the described in the literature and (d) from development comparison on the GE with the GC, on 6months. With these data was concluded that an early intervention participate of the evolution in the development in the infants at risk, therefore it is not the only reason that acts in this development and that the home intervention improves the interaction between the therapist with the infants. And was concluded that its family, mainly the mother, that is the most important in this stimulation process.
Early home stimulation: an intervention program and its analysis in at-risk infants aged 0 to 6 months
Keywords: Estimulação precoce; Bebês de risco; Anóxia perinatal; Atendimento domiciliar; Desenvolvimento infantil; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO